Assessing the Effect of Air Blast Loading on the Structural Behaviour of Reinforced Concrete Column. - Kasyage, Abubakali (Kabale University, 2025)
This project investigated the effect of air blast loading on the structural behavior of reinforced concrete (RC) columns, essential components in various infrastructures. With increasing concerns over safety from explosive threats, understanding how RC columns respond to dynamic loading is crucial for enhancing structural resilience. The study utilized advanced finite element analysis and the CONWEP method to generate pressure-time histories for different explosive scenarios, which were then applied to RC column models in Abaqus. The research focused on evaluating key parameters such as peak pressure, impulse duration, and the columns' resulting deformation and failure modes. Findings indicate that increased charge weights and reduced stand-off distances significantly elevate the risk of shear and flexural failures. The study underscores the importance of incorporating nonlinear material behavior in simulations to accurately predict structural responses. Ultimately, this research aims to provide insights and design recommendations for improving the blast resistance of RC columns, contributing to safer urban environments against potential explosive threats.